Can someone simplify this boolean expressions?

here are some boolean expressions:

1.AB(A+B) (B+B) =

2.(A+C) (AD+AD) +AC + C =

3.A (A+B)+(B+AA)(A+B)=

4.AB+A(B+C)+B(B+C)=

5.B(A + C) + A(not)B + B(not)C+C =

6.(x + y ) (x +[not]y)([not]x + z ) =

7.xy+ (not)xz+yz =

Thank you very much ^_^

Update:

These are boolean expressions and some are not complicated( i think? XD ) i'm having a hard time

2 Answers

Relevance
  • Ray
    Lv 7
    8 years ago
    Favorite Answer

    To simplify Boolean expressions you must know the basic laws such as

    A + A = A

    A.A = A

    _

    A + A = 1

    _

    A.A = 0

    Thus for question 1

    AB(A + B)(B + B) = AB(A + B)(B)

    AB(A + B)(B + B) = AB(A + B)

    AB(A + B)(B + B) = ABA + ABB

    AB(A + B)(B + B) = AB + AB = AB

    Let me know if you want further help.

  • Anonymous
    8 years ago

    i'm sorry i can't help you but i just had to say : what the hell does that even mean? It looks complicated and scary lol

Still have questions? Get your answers by asking now.